2000
DOI: 10.1177/004051750007000910
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphologies of Polypropylene Fibers Studied by Atomic Force Microscopy

Abstract: Surface morphologies of compact-spun polypropylene fibers spun with varying spin and tow draw ratios are characterized with atomic force microscopy (AFM). The surface structures are correlated to x-ray diffraction, birefringence, and fiber tenacity: The surface morphology of as-spun fibers is spherulitic at spin draw ratios lower than 500. With increasing spin draw ratio, the morphologies develop into epitaxially crystallized struc tures, and a shish-kebab morphology is evident with spin draw ratios higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Primary research in this area on AFM has been concentrated on as‐cast polymers that form under little or no deformation field 1–3. There are very few reported studies on the influence of processing history on the structural hierarchy developed on surfaces of injection molded parts,4, 5 melt spun fibers6, 7 as well as on surfaces of isothermally stretched films 8. Effect of deformation at elevated temperatures has been studied by few investigators 8.…”
Section: Introductionmentioning
confidence: 99%
“…Primary research in this area on AFM has been concentrated on as‐cast polymers that form under little or no deformation field 1–3. There are very few reported studies on the influence of processing history on the structural hierarchy developed on surfaces of injection molded parts,4, 5 melt spun fibers6, 7 as well as on surfaces of isothermally stretched films 8. Effect of deformation at elevated temperatures has been studied by few investigators 8.…”
Section: Introductionmentioning
confidence: 99%
“…Primary research activities in this area have been concentrated on the isotropic as-cast polymers, including low-isotacticity polypropylene . Solid-state , and melt deformation effects have also been investigated. The effect of deformation at elevated temperature was studied in ref , with the effect of deformation to engineering strain 6 at 140 °C, 2 mm/min on stretched isotactic polypropylene film with isotactic index 94. This study revealed the presence of fibrillar structure with some grains that are proposed to have epitaxially grown on the shish crystals (microfibrils).…”
Section: Introductionmentioning
confidence: 99%
“…Figure D) for both PP and PP + ER are shown in Figure A and B. The simultaneous appearance of the equatorial and near-meridional components points to the bimodal crystalline orientation , with daughter or secondary lamellae growing epitaxially atop parent or primary lamellae oriented along the fiber c -axis as shown schematically in Figure D. The bimodal orientation originates from the deviation from the alternating sequence of right-handed and left-handed helices characteristic for the isotactic α-polypropylene chains in its monoclinic unit cell. , The synchrotron nXRD here was effective for identification of this particular structural feature in a single fiber, which is otherwise challenging to detect due to the relatively small number and size of the crystallites within the semicrystalline matrix.…”
Section: Results and Discussionmentioning
confidence: 95%